2006
DOI: 10.1128/iai.01985-05
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Interleukin-10 Impair Resistance to Pulmonary Coccidioidomycosis in Mice in Part through Control of Nitric Oxide Synthase 2 Expression

Abstract: We have shown previously that there is a direct correlation between IL-10 levels and susceptibility to Coccidioides immitis peritonitis in C57BL/6 (B6), DBA/2, and BXD recombinant inbred mice. We now show that B6 mice are also more susceptible to C. immitis pneumonia and that interleukin-10 (IL-10)-deficient (IL-10 ؊/؊ ) B6 mice are more resistant to C. immitis pneumonia. In addition, we established that high levels of IL-10 are sufficient to make genetically resistant mice susceptible to both C. immitis perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 65 publications
(43 reference statements)
3
39
0
Order By: Relevance
“…4 and 6). This was a surprising result, because B6 mice make more IL-10 than resistant DBA/2 mice (67), and high levels of IL-10 are detrimental in this infection (17). One possible explanation is that the mutant mice also made more of some potentially protective cytokines, such as IFN-␥, GM-CSF, and IL-17 and IL-23.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…4 and 6). This was a surprising result, because B6 mice make more IL-10 than resistant DBA/2 mice (67), and high levels of IL-10 are detrimental in this infection (17). One possible explanation is that the mutant mice also made more of some potentially protective cytokines, such as IFN-␥, GM-CSF, and IL-17 and IL-23.…”
Section: Discussionmentioning
confidence: 89%
“…In further support of genetic factors being important in determining the immune response to infection and therefore susceptibility, we discovered that inbred mice also vary greatly in their susceptibility to coccidioidomycosis (15). Susceptible mice make more interleukin 4 (IL-4) and 17), and IL-10-deficient C57BL/6 (B6) mice are more resistant to infection than B6 mice (18).…”
mentioning
confidence: 99%
“…The images were obtained from the CDC (http://phil.cdc.gov/phil/details.asp). This figure was previously published in the Journal of Fungi [70]. …”
Section: Dimorphismmentioning
confidence: 99%
“…A broad-spectrum NOS inhibitor increased the susceptibility of DBA/2 mice to C. immitis [69]. In contrast, a Nos2 mutant mouse strain was not more susceptible [70]. However, that mutation was made in C57BL/6 mice, which themselves make very little NO in response this infection [69].…”
Section: Immunologymentioning
confidence: 99%
“…Work with the pathogenic fungi Histoplasma capsula-tum (2,24), Paracoccidioides brasiliensis (17,22), Coccidioides immitis (15), and Cryptococcus neoformans (31) has shown that the macrophage nitric oxide-producing enzyme, inducible nitric oxide synthase (iNOS), promotes host clearance of invading fungi. Conversely, each of these fungal pathogens has evolved the means to subvert nitric oxide production or resist killing by nitric oxide (6,10,13,23,25,30,32,37).…”
mentioning
confidence: 99%